THE EFFECTIVENESS OF MEMORIES AND DRAW TOWARDS STUDENTSâ€™ MOTIVATION IN READING COMPREHENSION - M. Asrul Hasby; Taufik Iswara (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2019)
This research was aimed to find out â€œThe Effectiveness of Memories and Draw Towards Studentsâ€™ Motivation in Reading Comprehensionâ€. The research was experimental research in form of quasi-experimental and the design that was used was the non-equivalent control group design. The population of this research was the second grade students of SMP Al-Ashriyah Sesela which consisted of two classes. The samples were VIII A as experimental class, and VIII B as control class where experimental class was treated by using Memories and Draw, and control class was treated by using matching picture. The data was analyzed using descriptive statistic (mean score, median, mode, and standard deviation). The researcher found that the motivation of the second grade students in reading comprehension effective by using Memories and Draw technique by the increase of mean score of experimental class that is 50.2 in the pre-test and 73.6 in the posttest. The result of the research was significant because the t-test also showed that Memories and Draw method effective to improve studentsâ€™ motivation in reading comprehension especially in reading descriptive text, because the value of t-test = 2.705 > t-table = 1, 697. It means that memories and draw towards studentsâ€™ Motivation in reading comprehension at second grade of SMP Al-AsriyahSesela was accepted. Therefore, using Memories and Draw hasÂ  effective on the studentsâ€™ motivation in reading comprehension, so it is recommended to the teachers to use Memories and Draw to improve their studentsâ€™ motivation in reading comprehension.